International Language Poetry: Radical Poetics in Charles Bernstein and Andrzej Sosnowski - Cieślak-Sokołowski, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The article discusses two linguistic poetry projects—that of the American poet Charles Bernstein and that of the Polish poet Andrzej Sosnowski. The main focus is on those poems by both poets which draw inspiration from the early modernist tradition of avant-garde and experimental literature. At the same time, the keystone of both works reveals itself to be—in reference to Ezra Pound’s poetic project—the belief that a poem is not so much a record of the poet’s experiences and emotions, but rather a distinct field capable of effectively assimilating and absorbing various elements (such as vocabularies, language styles, discourses). In this light, when closely examined, Bernstein’s and Sosnowski’s poems emerge as a late-modern attempt to contain the oversimplified, ideologized images of contemporary reality within an effectively polyphonic poetic text. This is because the author attempts to demonstrate that a difficult poem, employing avant-garde techniques, does not have to be merely a sterile formalist exercise. Instead, innovative poetic practices continue to have an important role, particularly if we shift our focus from political and journalistic declarations to the politicization of form. Poetry that still seeks stylistic and formal innovations can suggest alternative approaches to readers regarding the oversimplified methods of shaping social formations.